ROLE OF BASE PLATFORM TO PREPARE PARPATI KALPANA W.S.R. TO RASA PARPATI (International Journal of Ayurveda and Pharma Research, 2021)
Parpati Kalpana is one of the famous Kalpanas of Rasashastra which is widely used and considered as a boon for digestive disorders. The Parpati name is given to this Kalpana as per its Papad or Parpata – thin flake – like appearance. Parpati Kalpana is mainly divided into Sagandha and Nirgandha Parpati Kalpana. Rasa Parpati is the type of Sagandha Parpati Kalpana. To prepare Parpati kalpana, at least one ingredient should get liquefied at normal heating and should get solidified when it gets cooled down, not only that, to get the thin flake like structure specific pressure needs to be applied. In present study Rasa Parpati was prepared by using Samaguna Kajjali (Equal quantity of Parada and Gandhaka) and to check the cooling effect and the role of base platform; here three different platforms were made i.e. cow dung and wet clay mixed platform, only wet clay platform (Earthen platform) and ice block platform. Total nine samples of Rasa Parpati were prepared, three on each platform to check which platform is convenient to prepare Rasa Parpati. The average thickness of Rasa Parpati was found minimum (2.83 mm) on cow dung and wet clay mixed platform whereas the maximum (4 mm) on ice block platform i.e. 4 mm. Average thickness of Rasa Parpati made on earthen platform was 3.57 mm which is thicker than the Cow dung and wet clay mixed platform and thinner than the ice cube platform. Which indicates the best platform to make thinnest Parpati is cow dung and wet clay mixed platform.